Titanium Dioxide 2017
DOI: 10.5772/intechopen.68603
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Reduced Rutile Titanium Dioxide Photocatalyst

Abstract: For TiO 2 photocatalysts, recombination of photoexcited electrons and holes would occur in crystalline defects such as oxygen vacancies, Ti 3+ ions, and surface states. Therefore, it is believed that the density of crystalline defects should be decreased to improve the photocatalytic activity of TiO 2 particles. Contrary to this common knowledge, the introduction of crystalline defects by hydrogen reduction treatment is shown to increase the lifetime of photoexcited electrons in rutile TiO 2 photocatalysts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This would be because the doped chromium species work as recombination centers. The photocatalytic activity of nondoped TiO 2 under UV irradiation was enhanced by electron doping with H 2 treatment as reported previously, ,, but it did not work under visible light irradiation unlike the “black” TiO 2 prepared by H 2 treatment …”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…This would be because the doped chromium species work as recombination centers. The photocatalytic activity of nondoped TiO 2 under UV irradiation was enhanced by electron doping with H 2 treatment as reported previously, ,, but it did not work under visible light irradiation unlike the “black” TiO 2 prepared by H 2 treatment …”
Section: Resultssupporting
confidence: 75%
“…In the case of nondoped rutile TiO 2 photocatalysts, the enhanced photocatalytic activity by H 2 reduction treatment is explained by the increase in electron density in the CB and shallow energy levels, which provide efficient charge separation by built-in potential and fast transport of photogenerated electrons. ,, In this study, we found that the H 2 reduction treatment decreased the midgap states working as deep traps of photoexcited electrons, and the radiative recombination between the deeply trapped electrons and the VB holes. As the H 2 reduction treatment increases the concentration of electrons, the traps at deep levels have already filled with the electrons before photoirradiation .…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Figure 23(a) shows calcination in air, peak at 529.80eV was reduced because high calcination temperature reduced lattice oxygen due to thermal stress, these effect caused by the rapid change in Ti-O-Ti network, whereas calcination under H 2 flow in the system, which could create more oxygen vacancies then observation area of peak centered at 531.3eV was raised, which is shown in Figure 23(b) Moreover, an electron from hydrogen through surface lattice oxygen then electron was released and transferred to Ti 4+ and then Ti 4+ received electron, so Ti 3+ was formed [28,52,68,69]. However, P25-TiO 2 was calcined in air with different temperature, which found the concentration of oxygen vacancies slightly changed because of additional oxygen in the system, which are shown in Figure 24.…”
Section: Ti2pmentioning
confidence: 97%